Integration of Social Regulations and Zakat Management Regulations as National Efforts to Alleviate Poverty - Muh, Muhaimin; Munir, Sirajul (UIN Sunan Kudus, 2023)
The primary responsibility of the government is to safeguard the best interests of all citizens. In Indonesia, where the majority of the population follows Islam, the principles of poverty eradication through social safety system align with the constitutional guidelines. Among these principles are social assistance and mustahik Zakat. However, the process of obtaining accurate data on beneficiaries of social assistance often encounters challenges, leading to the emergence of inaccurate information. This is in line with Article 28 of Law of the Republic of Indonesia Number 13 of 2011 concerning Handling The Poor, where the government is required to develop a comprehensive plan to aid the impoverished. It also involves establishing a database of those in need and implementing efficient application methods. From this context, the data collection issues hinder the ability of the government to achieve critical objectives, such as poverty reduction and enhancing the overall well-being of the population. Therefore, this study aims to determine a position where Islamic and state law agree on the patterns of helping poor people eradicate poverty toward the coexistence of social aid and mustahik Zakat data, using a normative legal method. The results showed that a single set of data should include both the people obtaining social aid and mustahik Zakat, for poverty reduction to be successful and progressive. For data to be integrated, the rules guiding the agreement of everyone should also be emphasized, to ensure that poor people were obtaining help from social services or Zakat mustahik. This enabled the easy operation of programs, to help affected people eradicate poverty.